Cultural Sensitivity and Ambiance in Indonesian Restaurants: The Mediating Role of Customer Satisfaction on Retention in Taiwan - Mujahida, Sitti; Fatmasari, Fatmasari; Azizurrohman, Muhammad (APMBA (Asia Pacific Management and Business Application), 2024)
This study explores the effects of food quality, service quality, pricing strategy, and ambiance on customer retention in Indonesian restaurants in Taiwan, with customer satisfaction as a mediating variable. This study also investigates the moderating role of cultural similarity in this relationship. A structured survey was conducted in a quantitative study design, collecting data from 400 international customers of Indonesian restaurants in Taiwan. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was used to analyze the data. The results showed that food quality and pricing strategy significantly increased customer satisfaction. In addition, service quality and ambiance had no significant contribution to customer satisfaction. Furthermore, cultural similarity strengthened the relationship between food quality and customer satisfaction. Finally, customer satisfaction had a significant effect on customer retention. This study provides important insights for Indonesian restaurant owners in Taiwan, emphasizing the important role of service quality and restaurant ambiance in addition to food quality and price to support customer satisfaction and thus increase customer retention.